A simple strategy to construct cobalt oxide-based high-efficiency electrocatalysts with oxygen vacancies and heterojunctions. (5th December 2019) - Chen, Junwei; Wang, Fangmu; Qi, Xiaopeng; Yang, Hui; Peng, Bojun; Xu, Liang; Xiao, Zongliang; Hou, Xinmei; Liang, Tongxiang
Abstract: Bare nonprecious metal oxides are generally considered to have low HER activity, but they have the advantages of abundant resources and low cost. Herein, a facile strategy to construct abundant oxygen vacancies with heterogeneous structures of oxygen-vacancies CoFe2 O4 /oxygen-vacancies cobalt oxides/nickel foam (Ov-CoFe2 O4 /CoOx /NF) is developed using gas-phase cation exchange. Benefiting from abundant oxygen vacancies, the strong interfacial coupling effects between oxygen-vacancies CoFe2 O4 (Ov-CoFe2 O4 ) and oxygen-vacancies cobalt oxides (Ov-CoOx ), a nanorod structure and the highly conductive nickel foam support, Ov-CoFe2 O4 /CoOx /NF exhibits a low overpotential of 59 mV and achieved a current density of 10 mA cm −2 in a 1 M KOH solution. Ov-CoFe2 O4 /CoOx /NF//Ov-CoFe2 O4 /CoOx /NF exhibits a low water splitting voltage of 1.51 V at 10 mA cm −2 . Density functional theory calculations suggest that oxygen vacancy and interfacial coupling effects can both improve conductivity of electrocatalysts. This study provides a facile design for simultaneous realization of oxygen vacancy modification and heterostructure, which may become a simple strategy to use oxides to improve HER performance. Graphical abstract: Image 1 Highlights: A simple strategy to achieve oxygen vacancy modification and a heterostructure. Synergistic effect lead to excellent alkaline HER activity. 3D self-supported binder-free integrated electrode. An effective strategy to improve oxides HER performance.